Evidence of validity of the instrument interRAI emergency screener for psychiatry for the brazilian context (Research, Society and Development, 2021)
Objective: The aim of this study was to carry out the translation and present the evidence of validity of the Brazilian version of the interRAI Emergency Screener for Psychiatry (ESP). Method: this is a cross-sectional study conducted in a municipal hospital in the metropolitan region of Porto Alegre, Rio Grande do Sul. A total of 161 patients were evaluated in the first 24 hours of emergency arrival using ESP. Exploratory factor analyses of the sections of the instrument and reliability analyses were conducted using Cronbach's alpha and McDonald's Omega. Results: the analyzes suggested a factorial structure adequate to the purpose of the instrument, with two sections (Mental State Indicators and Harm to Self and Others) having a two-factor solution, contrary to the expected one-factorial expectation. However, the two-factor sections have theoretical interpretability and consistency. The factor loadings of the items were adequate, all with values equal to or greater than 0.30. The interpreted factors showed internal consistency, assessed by Cronbach's Alpha and McDonald's Ommega indices, with values ranging between 0.60 and 0.94. Conclusion: the Brazilian version of the interRAI Emergency Screener for Psychiatry (ESP) demonstrates adequate psychometric properties through the internal structure of the instrument. Future studies should investigate the relationship of the scores produced by the instrument with clinical diagnosis and with covariates relevant to mental health outcomes.